The photodissociation dynamics of OCS at 248 nm: the S((3)P(J)) atomic angular momentum polarization. - Brouard, M; Quadrini, F; Vallance, C (2007)
The dissociation of OCS has been investigated subsequent to excitation at 248 nm using velocity map ion imaging. Speed distributions, speed dependent translational anisotropy parameters, and the atomic angular momentum orientation and alignment are reported for the channel leading to S((3)P(J)). The speed distributions and beta parameters are in broad agreement with previous work and show behavior that is highly sensitive to the S-atom spin-orbit state. The data are shown to be consistent with the operation of at least two triplet production mechanisms. Interpretation of the angular momentum polarization data in terms of an adiabatic picture has been used to help identify a likely dissociation pathway for the majority of the S((3)P(J)) products, which strongly favors production of J=2 fragment atoms, correlated, it is proposed, with rotationally hot and vibrationally cold CO cofragments. For these fragments, optical excitation to the 2 (1)A(') surface is thought to constitute the first step, as for the singlet dissociation channel. This is followed by crossing, via a conical intersection, to the ground 1 (1)A(') state, from where intersystem crossing occurs, populating the 1 (3)A(')1 (3)A(")((3)Pi) states. The proposed mechanism provides a qualitative rationale for the observed spin-orbit populations, as well as the S((3)P(J)) quantum yield and angular momentum polarization. At least one other production mechanism, leading to a more statistical S-atom spin-orbit state distribution and rotationally cold, vibrationally hot CO cofragments, is thought to involve direct excitation to either the (3)Sigma(-) or (3)Pi states.